1987
DOI: 10.1002/asna.2113080206
|View full text |Cite
|
Sign up to set email alerts
|

Combined UBV and uvby photometry of open clusters. I. NGC 1502

Abstract: For at all 24 stars in the field of the heavily reddened open cluster NGC 1502 we obtained UEYand uvby photometry. 19 of these stars we classified definitely as members. From the photometric results we derived 1.1 x lo7 years as the cluster age, 960 pc as its distance, and (E(B -5) = 0.78 mag as mean reddening of the cluster. From the reddening of the foreground stars we evaluated that the intracluster reddening has to be smaller than 0.2 mag. The value of the colour excess ratio E(h -y)/E(B -V ) = 0.770 leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The mean airmass over the duration of each exposure was between 1.2 and 1.3. Two standard fields of NGC 1502 (Reimann & Pfau 1987) were taken before and after the observations.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The mean airmass over the duration of each exposure was between 1.2 and 1.3. Two standard fields of NGC 1502 (Reimann & Pfau 1987) were taken before and after the observations.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…NGC 1502: there are several photometric studies of this cluster in the literature (Purgathofer 1961;Reimann & Pfau 1987;Tapia et al 1991;Delgado et al 1992;Crawford 1994), but except Purgathofer (1961), all studies are limited to about 12th magnitude. A study of proper motions and the membership probability was carried out by Hopmann (1958).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the data for NGC 1502 fits the average relation quite well. When one plots the Delgado et al (1992) or the Reimann and Pfau ( 1987) data, the data points fall somewhat off of the relation. The Delgado et al data are shown in Fig.…”
Section: The Observationsmentioning
confidence: 95%
“…In addition to their data and their analysis of it in terms of interstellar reddening, distance modulus, and cluster age, Reimann and Pfau (1987) give references to other operated by AURA, Inc., under cooperative agreement with the National Science Foundation. data on the cluster stars, in particular polarimetry and proper motions, and they discuss some of the properties of the cluster as well.…”
Section: Introduction Ngc 1502 Is a Relatively Young Open Cluster In mentioning
confidence: 99%